PEMANFAAT AN LIMBAH lKAN DALAM RANSUM UNTUK MENINGKATKAN PENDAPATAN PETANI PETERNAK AYAM BROILER DI DAERAH TEPUS, GUNUNG KIDUL, DIY - Astuti, Astuti (Universitas Negeri Yogyakarta, 2003)
This society servitude aims to use the fish waste in poultry feed to increase the income of fishermen in Baron, Tepus, Gunung Kidul, DIY. This purpose is designed into two activities namely, information delivery about the idea and advantages of using the fish waste; and the process of manufacturing the fish waste into fish flour is also introduced.Thirty fisherman joined with this program. The information delivery was conducted on 21 August 2002 and the pratical work of manufacturing fish flour was conducted on 21 November 2002 and at Baron meeting house, Tepus, Gunung Kidul, DIY.Result shows that the participants show positive response by collecting the fish waste and drying them up, the dry fish waste then blended to produce the fish flour.Key words: fish waste, poultry feed